Application of Information Technology in Sharia Accounting: A Strategy for Creating New Efficiency in Sharia Financial Institutions - Eka Ratna Glis Purnamasari; Maulana Syarif Afwa; Binti Nur Asiyah (International Journal of Economics (IJEC), 2026)
The digital transformation that has penetrated the world of accounting has also reached entities that adhere to Sharia principles, thus creating a need to understand how information technology can support efficiency without sacrificing inherent Islamic values. This study was conducted to examine the role of information technology including cloud computing, blockchain, and artificial intelligence in Sharia accounting information systems (AIS), as well as their implications for compliance with the principles of justice, trustworthiness, transparency, and the prohibition of riba (usury), gharar (gharar), and maysir (gambling). The approach used was qualitative descriptive through library research, reviewing books, journal articles, and regulatory documents relevant to Sharia accounting and accounting information systems. The study's findings demonstrate that the use of information technology can automate transaction recording, reduce human error, accelerate the preparation of financial reports, and strengthen the transparency and accountability of Sharia financial institutions. However, its implementation still faces several obstacles, including limited human resources with expertise in accounting and Sharia principles, high technology investment costs, data security threats, heterogeneity in global standards, and the complexity of adapting conventional systems to Sharia principles. This study is expected to enrich the conceptual discourse regarding the development of a sharia accounting information system that is efficient, transparent, and remains based on Islamic values